Pressure effects on the electronic, magnetic, thermoelectric, and thermodynamic properties of Mn2CoSi half‐metallic compound. Issue 4 (7th September 2020) - On, Vo Van; Nguyen, Duy Khanh; Hoat, D. M.; Ponce‐Pérez, R.; Rivas‐Silva, J. F.; H. Cocoletzi, Gregorio
Abstract: In this work, the pressure effects on the electronic, magnetic, thermoelectric, and thermodynamic properties of the half‐metallic full‐Heusler Mn2 CoSi compound are investigated using spin‐polarized first‐principles calculations. The material used is half‐metallic, with the spin‐up alignment being metallic and semiconductivity found in the spin‐down state, creating the perfect spin polarization of 100%. Ferromagnetic and spin‐flip energy gaps have values of 0.887 and 0.415 eV, respectively. The half‐metallicity is quite robust under high pressures. The magnetic properties of Mn2 CoSi follows the Slater‐Pauling rule, M t = Z  − 24, being produced mainly by the Mn and Co atoms, while the Si contribution is negligible. Thermoelectric properties' calculations indicate that the metallic behavior generates quite a small figure of merit, while large values close to unity can be obtained with the semiconductor nature. Finally, the Mn2 CoSi thermodynamic properties, including the Gibbs free energy, thermal expansion coefficient, bulk modulus, heat capacity, Grüneisen parameter, and Debye temperature, under different temperatures (up to 1000 K) and pressures (up to 50 K) are determined and discussed in detail. Abstract : This study demonstrated the spin‐resolved band structure and spin‐up Fermi surface of the Mn2 CoSi compound.